GE_GERICHTE P/8093/2020 vom 21. August 2024 - GE Cour de justice (2024)
IN DUBIO PRO REO;BRIGANDAGE;RECEL;VOL D'USAGE;FIXATION DE LA PEINE;CONCOURS D'INFRACTIONS;TORT MORAL | CP.140.al1; CP.160.al1; CP.172ter; LCR.94.al1; CP.47; CP.49.al1; CP.49.al2; CP.41.al1; CO.49